Evaluasi Program Praktek Pengamalan Ibadah Di Sekolah Dasar Ar-Raudah Bandar Lampung - Ayu, Sovia Mas (Universitas Islam Negeri Raden Intan Lampung, 2017)
Evaluation of the Worship Practice Program Program aims to provide an assessment of the implementation and achievement of program objectives. CIPP Model Stufflebeam is used in research to evaluate aspects of context (goals, guidance, and implementation), input aspects (materials, teachers, and students), process aspects (technical implementation of programs), and products or outputs (results). Analysis of research data using a descriptive qualitative approach. The data collection tool uses interviews and observations to assess teacher behavior by students, self-assessment questionnaires by students, and student behavioral assessment questionnaires by parents. The object of the study was 3 teachers, 55 students, and 55 parents of students. The evaluation results show that for the context and input aspects in the good category. Process evaluation is a good category, related to the timing of implementation and steps for implementing PPI activities in accordance with established guidelines. Product evaluation in sufficient categories means that students can be said to be quite good in religious behavior individually. While the assessment of indicators of religious behavior shows good categories.